Forest disturbance accelerates thermophilization of understory plant communities. (3rd June 2015) - Stevens, Jens T.; Safford, Hugh D.; Harrison, Susan; Latimer, Andrew M.; Gilliam, Frank
<x xml:space="preserve">Abstract</x> Canopy disturbance, created by the combination of fuel‐reduction treatments and wildfire, is likely to accelerate plant community shifts towards species from warmer regions via its effects on understory microclimate at small scales. Understory diversity can be enhanced by intermediate disturbance regimes that promote the coexistence of species with different biogeographic affinities. <boxed-text content-type="graphic" id="jec12426-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>